(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2016)
Erosion and accretion rate are found very high in the estuary of an active delta which can be observed by satellite imageries. According to the multispectral satellite imageries it is found that accretion of Domar Char (a little island belongs to Meghna estuary) was more than 1192 hectares in last 25 years. The study was conducted in five years interval from 1990 to 2015 using spatial analyst extension of ArcGIS. It is revealed that accretion rate is about 208 hectares/year and erosion is about 160 hectares/year, which indicates the dynamic nature of the island. According to Landsat imageries about 2500 hectares of land rose in five years (1990 to 1995) and again lost 2300 hectares of land in next five years (1995 to 2000). Though the total area of intertidal zone has decreased, the area of barren land, vegetation and sand dune has increased over the time. Asiat. Soc. Bangladesh, Sci. 42(2): 219-228, December 2016